Analysis of Students' Discriminatory Attitudes Towards Social Diversity (Case Study at the State Islamic University of North Sumatra) - Azizah Nur Khalisah Daulay; Mira Shaila Ardana; Muhammad Raja Muhibbullah; Ainul Mardiyah (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Social diversity is an undeniable reality in higher education settings, including at the State Islamic University of North Sumatra (UIN SU). This study aims to examine students’ attitudes toward social diversity, identify forms of discrimination, and explore how students respond to such experiences within the campus environment. Utilizing a qualitative approach, data were collected through observations and in-depth interviews with five students from various cultural and social backgrounds. The findings reveal that most students view diversity as a strength that enriches social experiences, promotes tolerance, and helps shape more open-minded character traits. However, subtle forms of ethnic-based discrimination still occur, often expressed through jokes, social stereotypes, or unequal treatment. Students generally respond to such discrimination with empathy, wisdom, and a willingness to foster dialogue and mutual understanding. Moreover, students’ experiences as newcomers highlight the importance of openness, adaptability, and respect in navigating a diverse social environment. This research emphasizes the need to create an inclusive campus atmosphere by strengthening character education, instilling values of tolerance, and increasing social awareness, so that diversity becomes a unifying force rather than a source of conflict.